2007
DOI: 10.1007/s10974-007-9102-0
|View full text |Cite
|
Sign up to set email alerts
|

Repeated bout effect on the cytoskeletal proteins titin, desmin, and dystrophin in rat skeletal muscle

Abstract: The aim of this study was to evaluate the effect of repeated bouts of exercise on the cytoskeletal proteins titin, desmin, and dystrophin. Rats were made to run downhill for 90 min 1 or 5 times separated by 14 days. Samples were taken from quadriceps femoris muscle 3, 48, 96 h and 50 days after the last exercise session and detected by quantitative PCR, histochemical stainings, and western blot analyses. Histopathological changes in titin, desmin, and dystophin stainings, an increase in beta-glucuronidase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 40 publications
3
47
0
Order By: Relevance
“…In a recent study, however, decrease in titin mRNA expression was observed 1 h after mild eccentric exercise (22). The present results are well in line with our previous observation from an animal study where titin mRNA expression did not change between 3 and 96 h after a single downhill running session but was increased 3 h after repeated exercise (31). The results together suggest that titin mRNA level is first decreased shortly after the eccentric exercise and possibly increased much later.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a recent study, however, decrease in titin mRNA expression was observed 1 h after mild eccentric exercise (22). The present results are well in line with our previous observation from an animal study where titin mRNA expression did not change between 3 and 96 h after a single downhill running session but was increased 3 h after repeated exercise (31). The results together suggest that titin mRNA level is first decreased shortly after the eccentric exercise and possibly increased much later.…”
Section: Discussionsupporting
confidence: 92%
“…The response of these proteins to the exercise is interesting already because of their location in the center of muscle action and their regulative possibilities related to that. It has been shown that in animal muscles mRNA levels of MLP, CARP, Ankrd2, and DARP are already elevated a few hours after exercise (19,31), and knockout studies of these proteins suggest their involvement in structural and regulatory roles in skeletal muscle (4). However, little is known about the effect of physical exercise on these proteins in human muscle.…”
mentioning
confidence: 99%
“…21 In contrast, after running exercise of a higher intensity, such as downhill running on a treadmill (13.5°decline, 17 m/min, 5-min bouts ϩ 2-min rest for 90 min), signs of titin protein loss have been detected in muscle fibers of the rat quadriceps femoris as analyzed by immunohistochemistry. 20 In the same study, one bout of downhill running did not affect titin gene expression, but five bouts of downhill running led to increases in titin mRNA levels, 20 supporting the idea that increased titin gene expression is a reaction to titin loss.…”
Section: Resultsmentioning
confidence: 92%
“…Cross-bridge kinetics are altered with aging (Larsson et al 1997;Thompson and Brown 1999;Lowe et al 2001;Frontera et al 2000;Hook et al 2001;Krivickas et al 2001) but whether these changes are directly responsible for an age-related increase in damage is unknown. Alternatively, desmin, titin, myosin light chain 2, tropomyosin, and α-actinin covary (either in concentration or isoform expression) with fiber MHC isoform content (Prado et al 2005;Chopard et al 2001;Schiaffino and Reggiani 1996) and have all been implicated in contraction-induced muscle injury (Meyer et al 2010;Lieber et al 1996;Koh and Escobedo 2004;Zhang et al 2008;Lehti et al 2007;Belcastro 1993;Childers and McDonald 2004). Finally, an age-related increase in susceptibility to damage could be due to environmental factors.…”
Section: Discussionmentioning
confidence: 99%